Strengthening and Deformation Mechanisms of Polycrystalline Platinum Based on Molecular Dynamics - Liu, Xin; Wei, Jinghui; Qiang, Wanzhi; Yue, Xiaodong; Yu, Huiping (physica status solidi (b), 2025)
Platinum is a noble metal with excellent electrical, optical, magnetic, and thermal properties and has far‐reaching applications in high‐temperature sensing and microelectronic devices. However, its mechanical properties at the nanoscale, especially the plastic deformation mechanism, still leave much to be explored. In this article, the tensile deformation behavior of polycrystalline platinum is investigated using a molecular dynamics approach, and the effects of strain rate and twinning on the strength and deformation mechanism of polycrystalline platinum are studied. The results show that an increase in strain rate increases the strength of the material; the plastic deformation mechanism of polycrystalline platinum is mainly dominated by dislocation slip and phase transition, accompanied by a small amount of twin generation. The role of twin boundaries is similar to that of ordinary grain boundaries, which hinders the movement of dislocations and thus affects the strength of platinum by refining the grains, and similar to the positive‐reversed Hall–Petch relationship, the existence of a critical twin thickness makes the strength of platinum reach its maximum. Moreover, it is found that Shockley dislocations are the main type of dislocations in polycrystalline platinum and play a dominant role in the plastic deformation of platinum.